Tinjauan Filsafat Hukuman dalam Islam terhadap Overspel dan Zina - Candra, Marli; Nadhiva, Nanda Pricilia (Al-Jinayah : Jurnal Hukum Pidana Islam, 2020)
The article aims to examine the legal philosophy that underlies the punishment of overspel written in article 284 of the Indonesia Criminal Code and zina in Islamic criminal law. Apart from studying its philosophical grounds, this article also seeks to understand the differences between overspel and zina. This article is a literacy study with interviewing several sources regarding their understanding of both overspel and zina. The results showed that there are connections between the community's view of the definition of zina and overspel. Overspel is a part of zina in its broader meaning. Zina categorised into zina al-lamam, namely all immoral act, zina muhshon, which is illegal sexual intercourse by married couples and zina ghairu muhshon for unmarried people. Overspel fall into the second category, namely zina muhshon. The legal philosophy that underlies zina is utilitarian principles, a punishment which aims to achieve future effects such as deterrent influence on society and a rehabilitative result for zina ghairu muhshon. Whereby overspel based on personal losses and regarded as a complaint offence.